2014
DOI: 10.1038/ejcn.2014.228
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of red meat with legumes in the therapeutic lifestyle change diet based on dietary advice improves cardiometabolic risk factors in overweight type 2 diabetes patients: a cross-over randomized clinical trial

Abstract: Dietary advice given for substitution of red meat with legume intakes within a TLC diet-improved lipid profiles and glycemic control among diabetes patients, which were independent from BMI change. This trial was registered in the Iranian Registry of Clinical Trials (http://www.irct.ir) as IRCT201202251640N7.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(93 citation statements)
references
References 29 publications
(41 reference statements)
2
88
2
1
Order By: Relevance
“…Two of these trials compared diet high in carbohydrates and DF to a diet high in mono unsaturated fatty acid diet [25,26], two compared a diet high in DF to a diet low in DF [27,28], three compared a diet high in cereal DF to a diet low in cereal DF [29][30][31], one compared a diet high in legumes to a diet low in legumes [32,33], and one compared a diet high in legumes to a diet high in cereal DF [32]. Most trials reported effects of DF on body weight, glycated haemoglobin, total cholesterol and other plasma lipids, plasma glucose and inflammatory markers.…”
Section: Randomized Controlled Trial Designmentioning
confidence: 99%
See 4 more Smart Citations
“…Two of these trials compared diet high in carbohydrates and DF to a diet high in mono unsaturated fatty acid diet [25,26], two compared a diet high in DF to a diet low in DF [27,28], three compared a diet high in cereal DF to a diet low in cereal DF [29][30][31], one compared a diet high in legumes to a diet low in legumes [32,33], and one compared a diet high in legumes to a diet high in cereal DF [32]. Most trials reported effects of DF on body weight, glycated haemoglobin, total cholesterol and other plasma lipids, plasma glucose and inflammatory markers.…”
Section: Randomized Controlled Trial Designmentioning
confidence: 99%
“…Two of these studies reported results on DF intake [18,33,34] and one study reported results for whole-grain, cereal DF and germ intake [12]. The most important results are discussed here, an overview of all studies can be found in Table 2.…”
Section: Prospective Cohorts Designmentioning
confidence: 99%
See 3 more Smart Citations